CFD Analysis of Operation Variables Impact on Microwave-Assisted Water Heating - Sulaiman, Muataz; Al-Salman, Ahmed Amer (Indonesian Journal Publisher, 2024)
Microwaves are the best technique for thermal sensitive materials processes performing high temperature with short time and less consumption of energy in addition to perfect control. Microwave heating technique has a faster heating rate compared to conventional heating methods. Microwave process consists QVF tube of 240 mm length and 17 mm internal diameter which located in the center of microwave oven (2.45GHz). The experiments involve the flow rate of the water is (2, 4, and 6) l/hr and the power of the oven are (500, 750, 1000, and 1250) W. The temperature of the water increased by increasing power of microwaves and reached 110 ˚C at 1250 W and 2 l/hr flowrate and it is increased with decreasing of flowrates. The experimental temperature measured by inferred camera. The temperature predicted by COMSOL are aligned closely at power 500 W and all flow rate. The results were analysed by COMSOL Multiphysics (v6.0).